Snobs and quétaines: Prestige and Boundaries in Popular Music in Quebec - Ollivier, Michèle (Popular Music, 2006)
This paper is a study of prestige and boundaries in Quebec French-language popular music. Based on interviews with artists, producers and critics conducted in the early 1990s, I argue that popular music in Quebec at that time remained divided along a symbolic boundary established in the 1960s between a highly prestigious group of songwriters/rock artists, who wrote and sang their own material, and a less prestigious group of interpreters/artistes populaires, who sang light pop songs or songs written by others. As predicted by Bourdieu, I show that artists in the most prestigious category were associated with privileged social groups and gained material and symbolic advantages from their prestige. They are more likely to receive honorific awards, to be invited to perform at special cultural events, to see their work recognised as 'important', and to persist over time. In opposition to Bourdieu, however, I argue that in the context of emerging nationalism, their songs were also perceived as providing collective benefits over and beyond class and gender divisions.